Implementation of the Family Health Promotion Model (FHPM) on Family Commitment in TB Transmission Preventive Action among the Heads of Familiesof TB Patients: A Structural Model - Martono Martono; Muhammad Akhyar; Eti Poncorini Pamungkasari; Anik Lestari; Sapja Anantanyu; Retno Setyowati (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Tuberculosis (TB) transmission prevention centering on family is an effective strategy to suppress the emergence of new clusters of pulmonary TB transmission. The commitment of family heads and several factors are related to this action. This study was conducted to identify, examine, and analyze the determinants of family commitment in preventing the transmission of pulmonary TB. This study applied a quantitative cross-sectional approach to 170 family heads of pulmonary TB patients using proportionate simple random sampling. The family health promotion model (FHPM) was used to analyze family commitment determinants in preventing TB transmission. Data were collected using a questionnaire. SEM analysis was utilized to determine the paths and the relationship between family function, perception of the disease transmission risk, as well as family support, and commitment to action to prevent TB transmission. This study recorded that 50.6% of respondents were male with an average age of 46.75 ± 46 and an age range of 36-55 years, 53% had a high school education; 25.9% were self-employed; had an average decent living need of 1.93 ± 0.85, 75.3% had nuclear family, and 47.1% were from patriarchal family. Model fit was achieved in the structural equation (Chi-square (χ2) = 173.44; df = 71, RMSEA = 0.072≤ 0.08; GFI = 0.90≥ 0.90; RMR = 0.019≤ 0.05; NFI = 0.98≥ 0.90; CFI = 0.99≥ 0.90; TLI = 0.98≥ 0.95; IFI = 0.99≥ 0.90; PGFI = 0.59; PNFI = 0,76). All dimensions and item scales are significantly related to their respective latent constructs. All factors forming the FHPM framework have a significant positive direct effect between latent variables. Factors from the FHPM framework significantly (family function t = 8.74, perception t = 4.46, and family support t = 7.37) have an influence on commitment to action to prevent pulmonary TB transmission. Family function is the most powerful factor explaining commitment to preventive action. This study reveals the paths and influences of family function, perception, and support on a commitment to prevent pulmonary TB transmission through structural model analysis.